PERGESERAN KEKUATAN POLITIK DI DPRD PROVINSI JAWA TENGAH - Turtiantoro Turtiantoro (Politika: Jurnal Ilmu Politik, 2015)
The election 2009 is a quite phenomenal because the Democratic Party won the legislatif election the same President/Vice President election while the PDIP strunggle for the second time failed, where as in Central Jawa positions untenable. The election 2004 PDIP won 24 seats, 2009 23 seats and 2014 27 seats.The research is are qualitative case study approach. The main characteristic of are good case study is to demonstrate are deep understansing of the case.The results that the number of seats and party that is able to put cedres in DPRD Central Java Province in 2004 was 7 party in 2009 11 political party and 2014 there were 8 political parties all of wich affect the opportunity to occupy posutions in the Provincial Parliament Central Java. Keyword: Legislative, Electoral, Central Java.